Transitional Safeguarding in London Borough of Hackney: A Case Study. Issue 1 (1st January 2022) - Griffiths, Raynor
Abstract : The article reflects upon work undertaken to date to build more robust safeguarding mechanisms for young people aged 16 − 25 years old. Hackney is a diverse and vibrant London Borough, with an estimated population of 280, 000 people, of which 48% are under the age of 29. In recognition of this and national work identifying the 'gap' in safeguarding provision for 16 − 25 year olds, the City and Hackney Safeguarding Adults Board, with the Community Safety Partnership and Children's Partnership, set up a Task and Finish Group to address the challenge of Transitional Safeguarding. The article describes the processes adopted by the group to understand what the fundamental safeguarding issues are for young people living in Hackney. It presents key findings from the consultation and how these were subsequently used to influence developmental work regarding Transitional Safeguarding. Hackney was part of the Contextual Safeguarding Pilot and subsequently established a Context Intervention Unit. Influenced by the group's work, it brings together skills and knowledge from both children's and adults safeguarding services, to create a bespoke service for young people who may experience extra-familial abuse or exploitation.